2010
DOI: 10.1029/2009jc005872
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nonlinear energy transfer on short surface waves

Abstract: [1] The effects of nonlinear energy transfer on the development of the short wave spectrum are evaluated using a diffusion approximation and a modification of this approximation to include nonlocal effects. Both formulations were used to compute the evolution of a JONSWAP-type spectrum, and the results are compared with direct numerical simulations. Terms corresponding to each of these formulations were then incorporated into the wave action equation, and the resulting equation was numerically integrated using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Fueled by continuous input of energy from an ISW, resonant surface waves grow until they are dissipated by wave breaking or energy transfer to shorter waves via nonlinear hydrodynamic interaction. Lyzenga (2010) found that the energy transfer mechanism, in particular at X-band, also leads to larger modulation depths (or image contrasts) than predicted by previous SAR imaging theories regarding ISWs. However, we conjecture that wave breaking dominates dissipation of resonant waves and that scattering from breaking waves is the dominant contributor to the mechanism that results in large ISW radar signatures.…”
Section: Surface Wave Breaking Induced By Strong Iswsmentioning
confidence: 51%
See 2 more Smart Citations
“…Fueled by continuous input of energy from an ISW, resonant surface waves grow until they are dissipated by wave breaking or energy transfer to shorter waves via nonlinear hydrodynamic interaction. Lyzenga (2010) found that the energy transfer mechanism, in particular at X-band, also leads to larger modulation depths (or image contrasts) than predicted by previous SAR imaging theories regarding ISWs. However, we conjecture that wave breaking dominates dissipation of resonant waves and that scattering from breaking waves is the dominant contributor to the mechanism that results in large ISW radar signatures.…”
Section: Surface Wave Breaking Induced By Strong Iswsmentioning
confidence: 51%
“…It should be noted that other scattering theories, which do not involve wave breaking, have been developed to explain the often observed large radar signatures of ISWs. The SAR imaging theories for ISWs of Thompson (1988), Lyzenga (2010), Craig et al (2012), andChen et al (2017) all yield larger modulation depths than those predicted by the theory of Alpers (1985) and are thus closer to reality; but they all fail to predict the very large ISW radar signatures that are frequently observed. Thus, we conjecture that scattering from breaking waves must be included in a SAR imaging theory for ISWs.…”
Section: Summary and Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Energy in the surface wave field is slowly accumulated under the wind action over thousands of wave periods [11], being redistributed by nonlinear wave-wave interactions [54]. Interestingly, all that energy can be quickly cascaded down to turbulent scales and dissipation-owing to enhanced surface wave breaking from an ISW-within very short time scales (typically of the order of a single internal wave period, about 40 min).…”
Section: Discussionmentioning
confidence: 99%